The role of depressive symptoms in the interplay between aging and temporal processing - Giulia Buzi; Francis Eustache; Arnaud D’Argembeau; Thomas Hinault (Scientific Reports, 2023)
Abstract Temporal processing, the ability to mentally represent and process the dynamical unfolding of events over time, is a fundamental feature of cognition that evolves with advancing age. Aging has indeed been associated with slower and more variable performance in timing tasks. However, the role of depressive symptoms in age-related changes in temporal processing remains to be investigated. Therefore, the present work aims to shed light on the link between temporal processing and depressive symptoms, which are frequent with advancing age. We relied on the multicentric “Blursday Project” database, providing measures of temporal processing together with questionnaires investigating psychological wellbeing. Results reveal that aging influences several timing abilities, from the reproduction of short time intervals to verbal estimations of longer temporal distances. Furthermore, the slowing down of felt passage of time regarding the last few days with age was fully mediated by the intensity of depressive symptoms. Overall, these findings suggest that depressive symptoms may play a pivotal role in age-related temporal processing changes.